Model Pengukuran Tax Evasion berbasis Money Ethics dan Tax Morals - Agustin, Nito; Yanti, Yanti; Nasihin, Ihsan (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This study aims to measure tax evasion using money ethics and tax morals. The approach used is quantitative with a sample of 100 KPP Pratama employees of Karawang Regency. The analytical method uses regression with the help of the SmartPLS version 4.0 application. The results showed that money ethics has a significant effect on tax evasion, which means that the higher the nature of a person's money ethics, the higher the tendency to take tax evasion. While the conclusion regarding tax morale on tax evasion is found that tax morale does not significantly influence tax evasion, which means that a person's tax morale does not influence that person to commit tax evasion. An important suggestion for the DGT is that it is hoped that they can always maintain the good name of the institution so that public trust in the Directorate General of Taxation does not decrease so that it does not trigger tax evasion crimes so that tax revenues in Indonesia can always reach the revenue target.